Is Arthroscopic Release a Good Treatment Option in Adhesive Capsulitis of Shoulder Refractory to Non-Operative Treatment : Treatment Option in Adhesive Capsulitis of Shoulder Refractory - Nazir Gill, Usman; Raza, Javed Hassan; Sajid, Muhammad; Sohail, Muhammad Amir; Khan, Junaid; Ameer, Khalid (Pakistan Journal of Health Sciences, 2023)
Adhesive capsulitis, causing shoulder pain and limited mobility, is effectively treated with arthroscopic release preferred for its proven efficacy, minimal complications, and enhanced accessibility to the whole joint capsule. Objective: To assess the outcome of arthroscopic releases in patients suffering from adhesive capsulitis in whom non-operative treatment failed. Methods: This retrospective study was conducted at Jinnah Hospital in Lahore from 2019 to 2021, encompassing 38 shoulders that underwent surgery. Among the total cohort, 15 cases were associated with female patients, and 23 male patients. Surgical interventions were carried out with patients positioned in a beach chair orientation. The initiation of physical therapy occurred at the earliest possible juncture, and evaluation of functional outcomes was undertaken employing the UCLA criteria. Results: The mean age of the individuals included in the research cohort was 51 years, exhibiting a broad age distribution ranging from 29 to 73 years. Significant improvements in the range of motion were evident, with an average augmentation of 56.71° in abduction, 38.5° in external rotation, and an additional extension of eight vertebral levels in internal rotation. As per the UCLA scoring system, the results exhibited a notably positive profile, with 16 shoulders attaining an excellent rating (42%), 16 being categorized as good (42%), and six falling within the fair or poor category (15%). Notably, five patients encountered postoperative complications. Conclusions: Arthroscopic release demonstrated effective results in alleviating pain and improving range of motion, establishing its efficacy as a treatment for adhesive capsulitis.